1981
DOI: 10.1007/bf01308371
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and histopathological study on primary and secondary intestinal lymphangiectasia

Abstract: Jejunal endoscopy and histopathological study of biopsied specimens were performed to clarify states of jejunal mucosa and the mechanism of enteric protein loss in six patients with protein-losing enteropathy, including four patients with intestinal lymphangiectasia, one patient with constrictive pericarditis associated with dilated lymphatics of the intestine, and one patient with Budd-Chiari syndrome. Three cardinal endoscopic findings, scattered white spots, white villi, and chyle-like substances covering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 15 publications
1
37
0
1
Order By: Relevance
“…1A, B). However, endoscopy did not reveal scattered white spots, white villi, or chyle-like substances covering the mucosa, which are typical findings of PLE due to lymphangiectasia (7). The mucosal biopsy specimens of the duodenum and jejunum revealed villous atrophy, moderate inflammatory cell infiltration (T lymphocytes and plasma cells), and intraepithelial lymphocytes without lymphangiectasia or vasculitis ( Fig.…”
Section: A B C Dmentioning
confidence: 90%
“…1A, B). However, endoscopy did not reveal scattered white spots, white villi, or chyle-like substances covering the mucosa, which are typical findings of PLE due to lymphangiectasia (7). The mucosal biopsy specimens of the duodenum and jejunum revealed villous atrophy, moderate inflammatory cell infiltration (T lymphocytes and plasma cells), and intraepithelial lymphocytes without lymphangiectasia or vasculitis ( Fig.…”
Section: A B C Dmentioning
confidence: 90%
“…One type had a diameter of less than 1 mm, while the other exceeded 3 mm in diameter. Asakura et al [21] reported three cardinal endoscopic findings in protein-losing enteropathy: scattered white spots, white villi and chyle-like substances covering the mucosa in the jejunum. In cases of sustained protein-losing enteropathy, capsule endoscopy may assist diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2). Biopsies from the duodenal wall did not show a typical picture of dilated lymphatics in the lamina propria, 3) but instead showed mildly dilated lymphatics in the deeper layer. Since no other underlying diseases, including inflammatory bowel disease, infection, celiac disease, etc., were found in the gastrointestinal system of the patient, his condition was diagnosed as PLE due to PIL associated with primary lymphedema in the extremities.…”
Section: Case Reportmentioning
confidence: 99%